Rare earth oxide improved cobalt-based alumina laser cladding coating and preparation method thereof
By adding lanthanum oxide and alumina to the cobalt-based alumina laser cladding coating, and using laser remelting and ion nitriding technology to form a nitriding layer, the lack of wear resistance and corrosion resistance of the coating at high temperatures is solved. The problem of the coating significantly improves the overall performance.
Patent Information
- Application Number
- CN202411369785.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art has shortcomings in improving the high-temperature wear resistance and molten aluminum corrosion resistance of cobalt-based alumina laser clad coating, especially in the long-term high temperature, the reinforcement layer is prone to peel off, resulting in poor coating quality.
The composite coating is prepared by laser cladding + laser remelting composite technology, and ionic nitriding is performed on the composite coating to form a 0.3-0.5mm nitriding layer.
The hardness, high temperature wear resistance and molten aluminum corrosion resistance of the composite coating are significantly improved, the growth of columnar crystals is reduced, and the generation of laser cladding cracks and pores are suppressed and eliminated.
Smart Images

Figure CN119411121A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser cladding, and in particular relates to a rare earth oxide improved cobalt-based aluminum oxide laser cladding coating and a preparation method thereof. Background Art
[0002] The integrated die-casting process is a disruptive technology in automobile manufacturing. In the past 50 years, the automobile body manufacturing process has always been dominated by robot welding after sheet metal stamping. The integrated die-casting technology has brought about a major change in the automobile body manufacturing process. The die-casting machine will replace the welding robot and become the core equipment for car manufacturing in the new energy field. In the working process of the die-casting machine, the die-casting mechanism, as one of the core components of the die-casting machine, is an indispensable part of the production of die-casting parts. In the working process of the die-casting mechanism, the aluminum alloy forming and manufacturing molds, die-casting melting cups, die-casting punches and other parts cannot avoid direct contact with molten aluminum.
[0003] Molten aluminum has high chemical activity and corrosiveness. It has good affinity with most metals and metal oxides and reacts chemically. During the process of melting aluminum alloy and forming aluminum parts, die-casting molds, injection cups, and injection punches that are in contact with aluminum will be corroded to a certain extent by the aluminum liquid. Aluminum alloy forming and manufacturing molds, injection cups, and injection punches are usually made of H13 steel, because H13 steel has good yield strength and hardness, and has good toughness and creep resistance at high temperatures. However, aluminum liquid erosion may cause a series of problems. After aluminum liquid erosion, the precision and service life of the forming mold will be reduced, and intermetallic compounds or pits will form on the mold surface, which may even cause the mold to fail. The intermetallic compounds generated after the surface of the forming mold is eroded by aluminum liquid will diffuse into the aluminum alloy products, which will cause the aluminum alloy products to contain impurities and fail to meet the quality requirements, thereby increasing production costs and low production efficiency.
[0004] Although great progress has been made in the research on the corrosion resistance of mold steel to aluminum liquid in China, there are still many problems. For example, by using special processes such as surface nitriding, carburizing and heat treatment to strengthen the surface of mold steel, the prepared strengthening layer is usually thin, which can achieve the effect of protecting the mold in a short time, but the strengthening layer will peel off under the erosion of high-temperature aluminum liquid for a longer time. There are also many problems in preparing the isolation layer on the surface of mold steel by chemical deposition and other methods. For example, the isolation layer prepared by metal composite materials can achieve the properties of high-temperature aluminum liquid corrosion resistance and wear resistance, but in actual engineering applications, more in-depth and extensive research is still needed. The isolation layer prepared by ceramic materials usually has the advantages of high hardness, strong wear resistance and extremely low solubility in aluminum liquid, but it also has the problems of high brittleness, poor impact resistance and easy cracking.
[0005] Laser cladding refers to a process in which a selected coating material is placed on the surface of the cladding substrate in different ways, and then irradiated by laser to melt it and a thin layer on the substrate surface at the same time, and then quickly solidified to form a surface coating with extremely low dilution and metallurgical bonding with the substrate, which significantly improves the wear resistance, corrosion resistance, heat resistance, oxidation resistance and electrical properties of the base surface, thereby achieving the purpose of surface modification or repair, which not only meets the requirements for specific performance of the material surface, but also saves a large amount of precious elements. Compared with surfacing, spraying, electroplating and vapor deposition, laser cladding has the characteristics of low dilution, dense structure, good bonding between the coating and the substrate, a wide range of application materials, and large changes in particle size and content. Therefore, the application prospects of laser cladding technology are very broad. The main characteristics of laser cladding technology are as follows: (1) The laser cladding layer is metallurgically bonded to the substrate, and the bonding strength is not less than 95% of the original substrate material, with good strengthening effect, high density of the cladding layer, and improved hardness, wear resistance and corrosion resistance at the same time; (2) The thermal effect on the substrate is small, and the deformation caused is also small. During the laser processing, the laser beam has high energy density, fast processing speed, and local processing, with no or minimal impact on non-laser irradiated areas. Therefore, the heat-affected area is small, the thermal deformation of the workpiece is small, and the subsequent processing volume is minimal; (3) The material range is wide, such as nickel-based, cobalt-based, iron-based alloys, carbide composite materials, etc., which can meet the requirements of different uses and take into account both internal performance and surface characteristics; (4) The cladding layer and its interface have dense structure, fine grains, no holes, no inclusions, cracks and other defects; (5) It can repair valuable parts and molds of large equipment that are partially worn or damaged, and achieve or even exceed the mechanical properties of the parent material, extend the service life, have a wide range of applications, high flexibility, and can adapt to various complex shapes; (6) For damaged parts, high-quality and rapid repairs can be achieved, reducing downtime due to failures and reducing equipment maintenance costs; (7) There is little environmental pollution, and no waste liquid or waste gas is discharged; the degree of automation is high, and the processing system can be designed to be fully computer-controlled; (8) Laser processing is non-contact processing, there is no direct impact on the workpiece, and therefore no mechanical deformation; there is no "tool" wear and no "cutting force" acting on the workpiece during laser processing.
[0006] Ceramic reinforcement phase is widely used in the preparation of composite coatings by laser cladding due to its good wear resistance, corrosion resistance and high temperature resistance, so as to improve the comprehensive performance of the cladding layer. However, preliminary experimental studies have shown that due to the large difference in parameters between the cladding material and the base material, and the rapid cooling rate during laser cladding, the generated gases (CO, CO2, etc.) do not have time to overflow and remain in the cladding layer to form pores, causing stress concentration around it, leading to the initiation of cracks. At the same time, the distribution of the reinforcement phase is uneven, forming a stacking structure in the cladding layer, so the density of the cladding layer is low and the forming quality is poor. To solve this problem, scholars have conducted a large number of experimental studies and found that the surface quality of the cladding layer can be improved to a certain extent by reasonably matching the ratio of the reinforcement phase and optimizing the process parameters, but the problem of pores inside the cladding layer is still inevitable.
[0007] Laser remelting technology is also a type of laser processing. It uses the high energy of the laser beam to quickly melt and solidify the material. When used as a post-processing process, it can re-melt the coating, which can effectively refine the grain structure, thereby facilitating the diffusion of elements, reducing segregation, and enhancing the surface hardness, wear resistance and corrosion resistance of the material. It is also beneficial for slag removal, gas homogenization, and healing of microcracks. Therefore, it is widely used in the post-processing of laser cladding and thermal spraying technologies. Summary of the invention
[0008] In order to solve the problems in the prior art, the present invention provides a rare earth oxide improved cobalt-based aluminum oxide laser cladding coating and a preparation method thereof.
[0009] The present invention solves the technical problem by adopting the following technical solutions:
[0010] The first object of the present invention is to provide a method for preparing a rare earth oxide improved cobalt-based alumina laser cladding coating, comprising the following steps:
[0011] Use H13 steel as the substrate, polish the surface of the substrate to make it smooth, and wipe it clean with acetone solution for later use;
[0012] Adding lanthanum oxide and aluminum oxide powders to cobalt-based coating powders, and ball-milling and mixing to obtain a composite coating;
[0013] The obtained composite coating is clad on the substrate using a laser cladding device;
[0014] The composite coating on the surface of the substrate is finished to a smooth surface, and then placed in a heat treatment furnace and kept at 400-550°C for 2-4 hours;
[0015] Use laser equipment to laser remelt the composite coating, with a laser power of 1000-1500W and a scanning speed of 10-20mm / s;
[0016] The composite coating is ion nitrided in an ion nitriding furnace to obtain a laser cladding coating. The volume ratio of nitrogen to hydrogen is 2:1, the nitrogen flow rate is 30-50 mL / min, the nitriding temperature is 500-600°C, the nitriding time is 2-4 h, and the nitriding pressure is 800-1000 Pa.
[0017] Furthermore, the laser cladding process is as follows: laser power is 3000-5000W, spot diameter is 2.8mm, scanning speed is 20-50mm / s, powder feeding rate is 20-50g / min, offset is 1-1.5mm, shielding gas is argon, powder feeding gas flow rate is 5-8L / min, shielding gas flow rate is 10-15L / min.
[0018] Furthermore, the laser cladding equipment is an infrared laser with a wavelength of 1070nm and a spot diameter of 2.8mm. The powder feeding nozzle in the laser cladding is a four-way coaxial powder feeding nozzle.
[0019] Furthermore, the nitriding depth after ion nitriding is 0.3-0.5 mm.
[0020] Furthermore, the mass fraction of lanthanum oxide in the coating is 0.5-2%.
[0021] Furthermore, the mass ratio of the cobalt-based coating powder, lanthanum oxide and aluminum oxide powder is 78-94.5:0.5-2:5-20.
[0022] Furthermore, the particle size of the cobalt-based coating powder, lanthanum oxide and aluminum oxide powder is 15-53 μm.
[0023] Furthermore, the ball milling time is 16-24h.
[0024] The second object of the present invention is to provide a rare earth oxide improved cobalt-based alumina laser cladding coating obtained by the above preparation method.
[0025] Furthermore, the cobalt-based coating powder has a composition of 53.5-60wt.% Co, 28-32wt.% Cr, 7.0-9.5wt.% W, 3.0wt.% Ni, 1.0wt.% Mn, and 1.0wt.% Si.
[0026] Furthermore, the cladding thickness of the laser cladding coating is 1-2 mm.
[0027] Compared with the prior art, the beneficial technical effects of the present invention are:
[0028] The present invention uses lanthanum oxide, cobalt-based and aluminum oxide powders as raw materials, obtains a lanthanum oxide-improved cobalt-based aluminum oxide composite coating through laser cladding + laser remelting composite technology, and then performs ion nitriding on the composite coating to obtain a 0.3-0.5mm nitriding layer on the surface. Aluminum oxide in the composite coating is used as a ceramic reinforcement phase, and aluminum oxide can significantly improve the hardness, high temperature wear resistance and molten aluminum corrosion resistance of the cobalt-based coating. Rare earth lanthanum oxide will form stable compounds with elements such as O and S in the cobalt-based alloy, and hinder the fusion and growth of aluminum oxide grains, which can promote the refinement of aluminum oxide grains and uniform distribution of components, and can also improve the cladding quality to make the organization more uniform, reduce the columnar crystals growing through the middle of the cladding layer, and also inhibit and eliminate the generation of laser cladding cracks and pores. Laser remelting technology further refines the grain structure, thereby facilitating the diffusion of elements, reducing segregation, and enhancing the surface hardness, high temperature wear resistance and molten aluminum corrosion resistance of the material. Surface ion nitriding technology can form a nitrided layer on the surface of the composite coating, which effectively improves the hardness, high-temperature wear resistance, fatigue strength and molten aluminum corrosion resistance of the composite coating surface.
[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention discloses a rare earth oxide-improved cobalt-based aluminum oxide laser cladding coating and a preparation method thereof, and the Vickers hardness of the composite coating obtained in each embodiment and comparative example. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope of protection that the present invention is intended to protect.
[0032] In addition, unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0033] Example 1
[0034] The H13 steel substrate was polished with 400-mesh sandpaper, and the surface oil was wiped off with acetone solution. Cobalt-based coating powder, lanthanum oxide and aluminum oxide powder with a particle size of 15-53μm were taken in a mass ratio of 93:0.5:6.5. The composition of the cobalt-based coating powder was: 54wt.% Co, 32wt.% Cr, 7.5wt.% W, 3.0wt.% Ni, 1.0wt.% Mn, 1.0wt.% Si; the above raw material powders were mixed in a ball mill and ball milled on a ball mill for 16h. At a laser power of 3000W, a scanning speed of 25mm / s, a powder feeding rate of 20g / min, an offset of 1mm, a powder feeding gas flow rate of 5L / min, and a protective gas flow rate of 10L / min, a laser cladding equipment was used to clad the composite powder on the H13 steel substrate to prepare a composite coating, and a 1.0mm thick composite coating was obtained. The composite coating was finished into a smooth surface and then placed in a heat treatment furnace and kept at 450°C for 2h. The composite coating was laser remelted using a laser device with a laser power of 1000W and a scanning speed of 20mm / s. The composite coating was ion nitrided using an ion nitriding furnace with a nitrogen to hydrogen volume ratio of 2:1, a nitrogen flow rate of 30mL / min, a nitriding temperature of 500°C, a nitriding time of 2h, and a nitriding pressure of 800Pa. The composite coating was subjected to a molten aluminum corrosion resistance test using a heat treatment furnace and a crucible with an experimental temperature of 700°C and a corrosion time of 24h. The surface of the obtained composite coating was smooth, with no peeling or pitting, and no aluminum sticking.
[0035] Example 2
[0036] The H13 steel substrate was polished with 400-mesh sandpaper, and the surface oil was wiped off with acetone solution. Cobalt-based, lanthanum oxide and aluminum oxide powders with a particle size of 15-53μm were taken at a mass ratio of 90:1:9. The composition of the cobalt-based coating powder was: 59wt.% Co, 28wt.% Cr, 9wt.% W, 3.0wt.% Ni, 1.0wt.% Mn, 1.0wt.% Si; the above raw material powders were mixed in a ball mill and ball milled on a ball mill for 18h. At a laser power of 3500W, a scanning speed of 35mm / s, a powder feeding rate of 50g / min, an offset of 1.5mm, a powder feeding gas flow rate of 8L / min, and a protective gas flow rate of 12L / min, a laser cladding equipment was used to clad the composite powder on the H13 steel substrate to prepare a composite coating, and a 2.0mm thick composite coating was obtained. The composite coating was finished into a smooth surface and then placed in a heat treatment furnace and kept at 400°C for 2.5 hours. The composite coating was laser remelted using a laser device with a laser power of 1200W and a scanning speed of 16mm / s. The composite coating was ion nitrided using an ion nitriding furnace with a nitrogen to hydrogen volume ratio of 2:1, a nitrogen flow rate of 36mL / min, a nitriding temperature of 530°C, a nitriding time of 2.5h, and a nitriding pressure of 860Pa. The composite coating was subjected to a molten aluminum corrosion resistance test using a heat treatment furnace and a crucible with an experimental temperature of 700°C and a corrosion time of 24h. The surface of the obtained composite coating was smooth, with no peeling or pitting, and no aluminum sticking.
[0037] Example 3
[0038] The H13 steel substrate was polished with 400-mesh sandpaper, and the surface oil was wiped off with acetone solution. Cobalt-based, lanthanum oxide and aluminum oxide powders with a particle size of 15-53μm were taken in a mass ratio of 86:1.5:12.5. The composition of the cobalt-based coating powder was: 55.5wt.% Co, 31wt.% Cr, 8wt.% W, 3.0wt.% Ni, 1.0wt.% Mn, 1.0wt.% Si; the above raw material powders were mixed in a ball mill and ball milled on a ball mill for 20 hours. At a laser power of 4000W, a scanning speed of 20mm / s, a powder feeding rate of 25g / min, an offset of 1.4mm, a powder feeding gas flow rate of 6L / min, and a protective gas flow rate of 14L / min, a laser cladding equipment was used to clad the composite powder on the H13 steel substrate to prepare a composite coating, and a 1.8mm thick composite coating was obtained. The composite coating was finished into a smooth surface and then placed in a heat treatment furnace and kept at 550°C for 3h. The composite coating was laser remelted using a laser device with a laser power of 1300W and a scanning speed of 14mm / s. The composite coating was ion nitrided using an ion nitriding furnace with a nitrogen to hydrogen volume ratio of 2:1, a nitrogen flow rate of 45mL / min, a nitriding temperature of 560°C, a nitriding time of 3h, and a nitriding pressure of 940Pa. The composite coating was subjected to a molten aluminum corrosion resistance test using a heat treatment furnace and a crucible with an experimental temperature of 700°C and a corrosion time of 24h. The surface of the obtained composite coating was smooth, with no peeling or pitting, and no aluminum sticking.
[0039] Example 4
[0040] The H13 steel substrate was polished with 400-mesh sandpaper, and the surface oil was wiped off with acetone solution. Cobalt-based, lanthanum oxide and aluminum oxide powders with a particle size of 15-53μm were taken at a mass ratio of 78:2:20. The composition of the cobalt-based coating powder was: 57.5wt.% Co, 29wt.% Cr, 8.5wt.% W, 3.0wt.% Ni, 1.0wt.% Mn, 1.0wt.% Si; the above raw material powders were mixed in a ball mill and ball milled on a ball mill for 24 hours. At a laser power of 5000W, a scanning speed of 30mm / s, a powder feeding rate of 30g / min, an offset of 1.2mm, a powder feeding gas flow rate of 7L / min, and a protective gas flow rate of 15L / min, a laser cladding equipment was used to clad the composite powder on the H13 steel substrate to prepare a composite coating, and a 1.5mm thick composite coating was obtained. The composite coating was finished into a smooth surface and then placed in a heat treatment furnace and kept at 480°C for 4 hours. The composite coating was laser remelted using a laser device with a laser power of 1500W and a scanning speed of 10mm / s. The composite coating was ion nitrided using an ion nitriding furnace with a nitrogen to hydrogen volume ratio of 2:1, a nitrogen flow rate of 50mL / min, a nitriding temperature of 600°C, a nitriding time of 4h, and a nitriding pressure of 1000Pa. The composite coating was subjected to a molten aluminum corrosion resistance test using a heat treatment furnace and a crucible with an experimental temperature of 700°C and a corrosion time of 24h. The surface of the obtained composite coating was smooth, with no peeling or pitting, and no aluminum sticking.
[0041] Comparative Example 1
[0042] The H13 steel substrate was polished with 400-mesh sandpaper, and the surface oil was wiped off with acetone solution. Cobalt-based powder with a particle size of 15-53μm was taken, and the composition of the cobalt-based powder was: 54wt.% Co, 32wt.% Cr, 7.5wt.% W, 3.0wt.% Ni, 1.0wt.% Mn, 1.0wt.% Si. At a laser power of 3000W, a scanning speed of 25mm / s, a powder feeding rate of 20g / min, an offset of 1mm, a powder feeding gas flow of 5L / min, and a protective gas flow of 10L / min, a laser cladding equipment was used to clad the composite powder on the H13 steel substrate to prepare a composite coating, and a 1.0 thick composite coating was obtained. The composite coating was finished to a smooth surface, and then placed in a heat treatment furnace and kept at 450°C for 2h. The composite coating was subjected to a molten aluminum corrosion resistance test using a heat treatment furnace and a crucible. The experimental temperature was 700°C and the corrosion time was 24 hours. The surface of the composite coating obtained had peeling and pits, and severe aluminum sticking.
[0043] Comparative Example 2
[0044] The H13 steel substrate was polished with 400-mesh sandpaper, and the surface oil was wiped off with acetone solution. Cobalt-based and alumina powders with a particle size of 15-53 μm were taken at a mass ratio of 80:20. The composition of the cobalt-based powder was: 59wt.% Co, 28wt.% Cr, 9wt.% W, 3.0wt.% Ni, 1.0wt.% Mn, 1.0wt.% Si. The above raw material powders were mixed in a ball mill and ball milled on a ball mill for 18 hours. At a laser power of 3500W, a scanning speed of 35mm / s, a powder feeding rate of 50g / min, an offset of 1.5mm, a powder feeding gas flow rate of 8L / min, and a protective gas flow rate of 12L / min, a laser cladding equipment was used to clad the composite powder on the H13 steel substrate to prepare a composite coating, and a 1.6mm thick composite coating was obtained. The composite coating was finished to a smooth surface and then placed in a heat treatment furnace and kept at 400°C for 2.5 hours. The composite coating was subjected to a molten aluminum corrosion resistance test using a heat treatment furnace and a crucible. The test temperature was 700°C and the corrosion time was 24 hours. The surface of the composite coating had peeling and pits.
[0045] By carrying out a molten aluminum corrosion resistance test experiment on the composite coating obtained in each embodiment and comparative example, by adding a composition of lanthanum oxide and aluminum oxide, lanthanum oxide forms a stable compound with elements such as O and S in the cobalt-based alloy, and hinders the fusion and growth of aluminum oxide grains, promotes the refinement of aluminum oxide grains and uniform distribution of components, and also improves the cladding quality to make the organization more uniform, reduces the columnar crystals growing through the middle of the cladding layer, and can also inhibit and eliminate the generation of laser cladding cracks and pores; at the same time, in conjunction with laser remelting technology, the grain structure is further refined, segregation is reduced, and high-temperature wear resistance and molten aluminum corrosion resistance are enhanced.
[0046] The Vickers hardness of the composite coatings obtained in each comparative example and experimental example was tested under a HV-1000 Vickers hardness tester, and the average Vickers hardness of each laser cladding coating was recorded. The test results are shown in the attached Figure 1 It can be seen that the average Vickers hardness of the laser cladding coatings in Comparative Examples 1-2 and Examples 1-4 are 610HV, 703HV, 905HV, 927HV, 946HV, and 972HV, respectively. The Vickers hardness of the composite coating obtained in the comparative example is much lower than that of the composite coatings in the embodiments of the present invention; while the addition of alumina in Comparative Example 2 significantly improves the hardness, high temperature wear resistance, and molten aluminum corrosion resistance of the cobalt-based coating. The present invention combines laser remelting technology and ion nitriding technology to form a nitriding layer on the surface of the composite coating, further improving the hardness of the composite coating surface, so that the Vickers hardness of the composite coating obtained in the embodiments of the present invention is much higher than that of the composite coating without laser remelting and ion nitriding technology.
[0047] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0048] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the enlightenment of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, which all fall within the protection of the present invention.
Claims
1. A method for preparing a rare earth oxide improved cobalt-based alumina laser cladding coating, characterized in that: The following steps are involved: Use H13 steel as the substrate, polish the surface of the substrate to make it smooth, and wipe it clean with acetone solution for later use; Adding lanthanum oxide and aluminum oxide powder to cobalt-based coating powder, and ball milling and mixing to obtain a composite coating; The obtained composite coating is clad on the substrate using a laser cladding device; The composite coating on the surface of the substrate is finished to a smooth surface, and then placed in a heat treatment furnace and kept at 400-550°C for 2-4 hours; Use laser equipment to laser remelt the composite coating, with a laser power of 1000-1500W and a scanning speed of 10-20mm / s; The composite coating is ion nitrided in an ion nitriding furnace to obtain a laser cladding coating. The volume ratio of nitrogen to hydrogen is 2:1, the nitrogen flow rate is 30-50 mL / min, the nitriding temperature is 500-600°C, the nitriding time is 2-4 h, and the nitriding pressure is 800-1000 Pa.
2. The method for preparing a rare earth oxide improved cobalt-based aluminum oxide laser cladding coating according to claim 1, characterized in that: The laser cladding process is as follows: laser power is 3000-5000W, spot diameter is 2.8mm, scanning speed is 20-50mm / s, powder feeding rate is 20-50g / min, offset is 1-1.5mm, shielding gas is argon, powder feeding gas flow rate is 5-8L / min, shielding gas flow rate is 10-15L / min.
3. The method for preparing a rare earth oxide improved cobalt-based aluminum oxide laser cladding coating according to claim 1, characterized in that: The nitriding depth after ion nitriding is 0.3-0.5 mm.
4. The method for preparing a rare earth oxide improved cobalt-based aluminum oxide laser cladding coating according to claim 1, characterized in that: The mass fraction of lanthanum oxide in the coating is 0.5-2%.
5. The method for preparing a rare earth oxide improved cobalt-based aluminum oxide laser cladding coating according to claim 1, characterized in that: The mass ratio of the cobalt-based coating powder, lanthanum oxide and aluminum oxide powder is 78-94.5:0.5-2:5-20.
6. The method for preparing a rare earth oxide improved cobalt-based aluminum oxide laser cladding coating according to claim 1, characterized in that: The particle sizes of the cobalt-based coating powder, lanthanum oxide and aluminum oxide powder are 15-53 μm.
7. A rare earth oxide improved cobalt-based alumina laser cladding coating obtained according to the preparation method according to any one of claims 1 to 6.
8. A rare earth oxide improved cobalt-based alumina laser cladding coating as claimed in claim 7, characterized in that: The cobalt-based coating powder has a composition of 53.5-60wt.% Co, 28-32wt.% Cr, 7.0-9.5wt.% W, 3.0wt.% Ni, 1.0wt.% Mn, and 1.0wt.% Si.
9. A rare earth oxide improved cobalt-based alumina laser cladding coating as claimed in claim 8, characterized in that: The cladding thickness of the laser cladding coating is 1-2 mm.